PROTOTYPE TELEDISPLAY BERBASIS SHORT MESSAGE SERVICE (SMS) SINGKAT BERCATUDAYA LISTRIK TENAGA SURYA - Iwa Sudradjat; Benny Nixon; Toto Supriyanto (Jurnal Poli-Teknologi, 2011)
This study aims to apply the Short Message Service (SMS) technology and solar power for a teledisplay. This system is useful to display some of the information specified in those places as appropriate wirelessly. Teledisplay is capable of displaying information on a Light Emmisi Diode (LED) matrix display with a length of information that can be displayed as 8 characters. Methods of delivery of information using SMS-Global System Mobile (GSM) with supplied by solar power. In this way the system can be placed anywhere because it does not depend on resources Statics Electrical. The device comes with adjustment system which allows you to adjust the intensity of the light intensity generated by the LED display will be adjusted so that the flame with environmental light conditions. The system is controlled by the two processors, the first processor set acceptance of information sent from the mobile phone and displays the information to display. The second processor is used to control the intensity level of Solar Cell and display. System built capable of displaying information transmitted via GSM cell phone with the power supply is obtained from a 30 watt solar cell and battery with a capacity of 45 ampere hours. Such systems are able to operate for three days while the weather was overcast. Keywords: Prototype, Teledisplay, Short Message Service (SMS), Solar cell. ABSTRAK Penelitian ini bertujuan menerapkan teknologi SMS dan listrik tenaga surya untuk sebuah teledisplay. Sistem ini berguna untuk menampilkan beberapa informasi ditempat-tempat tertentu sesuai keperluannya secara nirkabel. Teledisplay yang dimaksud berkemampuan menampilkan informasi pada display LED matrik dengan panjang informasi yang dapat ditampilkan sebanyak 8 karakter. Metode penyampaian informasinya menggunakan sistem SMS-GSM dan kebutuhan dayanya dicatu dengan pembangkit listrik tenaga surya. Dengan cara seperti ini sistem dapat ditempatkan dimana saja karena tidak tergantung dengan jarak atau sumber daya PLN. Perangkat ini dilengkapi dengan sistem penyesuai intensitas yang berguna untuk mengatur intensitas cahaya yang dibangkitkan oleh LED sehingga nyala display akan disesuaikan dengan kondisi cahaya lingkungannya. Sistem ini diatur oleh dua prosesor. Prosesor pertama mengatur penerimaan informasi yang dikirim dari handphone dan menampilkan informasi tersebut ke display. Prosesor kedua digunakan untuk mengontrol PLTS dan tingkat intensitas display. Sistem yang dibangun mampu menampilkan informasi yang dikirimkan melalui HP-GSM dengan catu daya diperoleh dari solar cell sebesar 30 watt dan baterai berkapasitas 45 amper jam. Sistem seperti ini mampu beroperasi selama 3 hari walaupun cuaca mendung. Kata Kunci: Prototype, Teledisplay, Short Message Service (SMS), Solar cell.